Analisis Komparatif Strategi Digital Marketing terhadap Keputusan Penggunaan Jasa Transportasi Online Gojek dan Grab di Kabupaten Karawang - Gina Maulidia; Ina Ratnasari (Jurnal Ilmiah Ekonomi Global Masa Kini)
The development of the transportation service industry is currently very fast. Especially in several big cities including Karawang district. Along with digital development, traditional transportation has become online transportation. Online transportation services that are currently very well known and often seen by the public are Gojek and Grab. This study aims to analyze digital marketing strategies on purchasing decisions in Karawang Regency. There are 100 respondents who use Gojek and Grab online transportation in Karawang Regency. This research uses quantitative methods. The analysis technique used is quantitative and descriptive analysis. In the verification analysis method used Simple Linear Regression analysis. The hypothesis sought is the partial effect or t-test and comparative t-test. In the test based on the research results it was found that there was a partial influence between digital marketing strategies on purchasing decisions. And based on the Comparative t-test research, there are differences between Go-Jek companies and Grab companies.